Modelling incoming radiation on a linear disturbance and its impact on the ground thermal regime in discontinuous permafrost. Issue 13 (27th March 2013) - Williams, T. J.; Quinton, W. L.
Abstract: Human‐induced disturbances and climate‐driven warming have resulted in unprecedented permafrost thaw in the zone of discontinuous permafrost. In a peatland environment south of Fort Simpson, NWT, we study the contribution of increases in incoming radiation to the ground surface, caused by removal of the tree canopy along linear disturbances, to changes in the ground thermal regime. A physically based understanding of thaw processes along linear disturbances is required in order to better understand the slow recovery of lines in this environment and to be able to efficiently reduce this impact during future resource exploration. The impact of increases in incoming radiation are examined through the development of a model (seismic incoming radiation model) to quantify these inputs, which are then used to drive the one‐dimensional coupled atmospheric‐surface‐subsurface model COUP. Results of this study show that incoming radiation (shortwave + longwave) is increased by up to 11% in a typical cutline compared to an undisturbed canopy. Relative to potential changes in near‐surface soil moisture, these increases in radiation do not appear to be an important control of permafrost thaw along linear disturbances. Field observations confirm that increased permafrost thaw on disturbances often occur irrespective of variations in incoming radiation. Copyright © 2013 John Wiley & Sons, Ltd.